EFFECTIVENESS IMPROVEMENT OF DISTANCE LEARNING OF STUDENTS: INTERNATIONAL AND LOCAL EXPERIENCE - Кліпа , Юлія (Socio-economic relations in the digital society, 2019)
the theoretical and practical aspects of distance learning in Ukraine and in the world are studied. The Ukrainian legal basis about distance learning was deeply analyzed. The author gives the history of development of distance learning and mass open online courses. The advantages and disadvantages of distance learning and mass open online courses were analyzed. Information about online resources for distance learning, where students can improve their personal knowledge was provided. Information about famous international free online courses is given by the author.